2016
DOI: 10.1002/jcla.21946
|View full text |Cite
|
Sign up to set email alerts
|

Variant RHD Types in Brazilians With Discrepancies in RhD Typing

Abstract: Our results show that discrepancies found in the serologic typing should be investigated by molecular methods in order to determine the D variant involved and also to distinguish between weak D and partial D. The knowledge of the distribution of weak D types and partial D among populations is important for D- patients and pregnant women management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
2
7
1
2
Order By: Relevance
“…Brazil represents one of the most diverse populations in the world, result of centuries of inter‐ethnical crossing of individuals from several continents . This ancestry diversity is a major factor underlying the peculiar distribution of RBC antigen phenotype among Brazilians, especially referring to the RH system, in which both African and European genomes are represented . This miscegenation can be clearly demonstrated by the allele distribution found in the present study, which comprised individuals with weak‐D phenotype.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Brazil represents one of the most diverse populations in the world, result of centuries of inter‐ethnical crossing of individuals from several continents . This ancestry diversity is a major factor underlying the peculiar distribution of RBC antigen phenotype among Brazilians, especially referring to the RH system, in which both African and European genomes are represented . This miscegenation can be clearly demonstrated by the allele distribution found in the present study, which comprised individuals with weak‐D phenotype.…”
Section: Discussionsupporting
confidence: 48%
“…This finding justifies why UK guidelines determine that patients exhibiting weak results in the D typing routine should be treated as D+ unless they are a female of childbearing age or a patient under chronic transfusion support . However, studies evaluating patients of mixed origin with discrepancies in D typing have shown that the distribution of RH variant alleles significantly differ from that observed among European‐descent individuals, mainly referring to the partial‐D phenotype, but also concerning the weak‐D phenotype . Transposing the recommendation of European transfusion guidelines to this different scenario may cause anti‐D alloimmunization, especially in services with no access to RH genotyping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines recommend the use of two selected anti‐D reagents to determine the D‐status, although DEL will not be detected and this strategy does not distinguish between partial and weak D . The selection of anti‐D reagents should be based on the prevalence and characterization of RHD variants in the population . In our Surinamese cohort, the most clinically relevant variants ( RHD*09.01, RHD*09.02, RHD*09.03.01 ) belonged to the weak D Type 4 cluster and should react weakly (i.e., less than 4+) with the majority of commercially available monoclonal anti‐D's.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is evidence that DEL RBCs can cause primary immunization of D negative patients through transfusion and can elicit a secondary anti‐D response in sensitized patients . The prevalence of individuals with an altered or negative D antigen expression varies significantly among different ethnic groups . Argentina's current population is the result of the intermixing, that started around 500 years ago, among Native Amerindians, Europeans, Africans and immigrants from other South American countries.…”
mentioning
confidence: 99%